Analysis of β-Galactosidase During Fruit Development and Ripening in Two Different Texture Types of Apple Cultivars - Yang, Huijuan; Liu, Junling; Dang, Meile; Zhang, Bo; Li, Hongguang; Meng, Rui; Qu, Dong; Yang, Yazhou; Zhao, Zhengyang (Frontiers in Plant Science, 2018)
Abstract β-galactosidase (β-Gal), one of the cell wall modifying enzymes, plays an important role in fruit ripening and softening. However, its role in apple fruit texture remains unclear. In this study, the role of β-Gal was analyzed in two apple cultivars, ‘Fuji’ and ‘Qinguan’, which are characterized by different fruit texture types, during fruit development and ripening. The firmness and pectin content of the fruits rapidly decreased and were much lower in ‘Fuji’ than in ‘Qinguan’ from 105 days after full bloom (DAFB). Transmission electron microscopy showed that the pectin-rich middle lamella was substantially degraded from 105 to 180 DAFB in the two apple cultivars. However, the degradation was more severe in ‘Fuji’ than in ‘Qinguan’. Subcellular localization analysis showed that the Mdβ-Gal1, Mdβ-Gal2, and Mdβ-Gal5 proteins were located in the cell wall. β-Gal activity continuously increased during all fruit developmental stages and was much higher in the mature fruits of ‘Fuji’ than in those of ‘Qinguan’, indicating that pectin was degraded by β-Gal. Consistent with the enzyme activities, expression levels of β-Gal genes (Mdβ-Gal1, Mdβ-Gal2, and Mdβ-Gal5) showed only slight changes from 60 to 105 DAFB but then dramatically increased until fruit ripening, with higher values in ‘Fuji’ than in ‘Qinguan’. Furthermore, we found that activities of deletion derivatives in the Mdβ-Gal2 promoter and transcript level of Mdβ-Gal2 were induced by the treatment with methyl jasmonate (MeJA) and ethylene (ETH) hormones. Two ETH and one MeJA hormone-responsive elements were identified by analyzing the promoter sequence. These results suggest that β-Gals, induced by ETH and MeJA, are involved in different fruit texture types of apple cultivars by influencing the degradation of pectin during the mature fruit stage.